Audit Quality Characteristics and Accounting Conservatism: Empirical Study in Indonesian Company - Krismiaji (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This research investigates the effect of audit quality on accounting conservatism in Indonesian companies. The research uses a sample of 510 observations of publicly listed companies on the Indonesian Stock Exchange for the fiscal year that ends on December 31, 2015 through 2019. Audit characteristics are proxied by the size of the public accounting firm (ASIZ), auditor specialization (ASP), and auditor tenure (ATEN), while accounting conservatism (ACON) is measured using the accrual method. The sampling process was carried out using a purposive method. The study finds that that auditor specialization and auditor tenure have positively affect accounting conservatism, while the size of the accounting firm negatively affects accounting conservatism. This result enriches the conservatism literature in the fair value accounting era which was adopted in 2012 especially in emerging market environment. Since accounting conservatism is one of agency problems solution as well as to protect investors, the result of this study may affect firms’ accountant to prepare financial information for interest users. The scope of the study period and the sample size due to empirical data conditions that do not meet the criteria and the use of only one measure of conservatism, namely the accrual method, may lead to the not optimal generalization of research results.